Bacillus firmus Strain I-1582, a Nematode Antagonist by Itself and Through the Plant - Ghahremani, Zahra; Escudero, Nuria; Beltrán-Anadón, Daniel; Saus, Ester; Cunquero, Marina; Andilla, Jordi; Loza-Alvarez, Pablo; Gabaldón, Toni; Sorribas, F. Javier (Frontiers in Plant Science, 2020)
Bacillus firmus I-1582 is approved in Europe for the management of Meloidogyne on vegetable crops. However, little information about its modes of action and temperature requirements is available, despite the effect of these parameters in its efficacy. The cardinal temperatures for bacterial growth and biofilm formation were determined. The bacteria was transformed with GFP to study its effect on nematode eggs and root colonization of tomato (Solanum lycopersicum) and cucumber (Cucumis sativus) by laser-scanning confocal microscopy. Induction of plant resistance was determined in split-root experiments and the dynamic regulation of genes related to jasmonic acid (JA) and salicylic acid (SA) by RT-qPCR at three different times after nematode inoculation. The bacteria was able to grow and form biofilms between 15 and 45 oC; it degraded egg-shells and colonized eggs; it colonized tomato roots more extensively than cucumber roots; it induced systemic resistance in tomato, but not in cucumber; SA and JA related genes were primed at different times after nematode inoculation in tomato, but only the SA-related gene was up-regulated at 7 days after nematode inoculation in cucumber. In conclusion, B. firmus I-1582 is active at a wide range of temperatures; its optimal growth temperature is 35 ºC; it is able to degrade Meloidogyne eggs, and to colonize plant roots, inducing systemic resistance in a plant dependent species manner.